The Influence of the Electoral System on Strengthening the Struggle against Soviet Power in Central Asia - Feruz Boboyev (International Journal on Integrated Education, 2022)
This article discusses the nature of the armed movement in Central Asia and the factors influencing the continuation of the struggle. Also in the world experience, the electoral system is a sign of democracy, but the unfair policy of the Soviet government in this matter is analyzed. As a result of the injustice of Soviet power in the electoral system, the rise of the armed movement in Central Asia was studied.